2017
DOI: 10.3138/jvme.0916-150r1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Tolerance of Ambiguity in Veterinary and Medical Students

Abstract: Current guidelines suggest that educators in both medical and veterinary professions should do more to ensure that students can tolerate ambiguity. Designing curricula to achieve this requires the ability to measure and understand differences in ambiguity tolerance among and within professional groups. Although scales have been developed to measure tolerance of ambiguity in both medical and veterinary professions, no comparative studies have been reported. We compared the tolerance of ambiguity of medical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This was supported in our previous study that compared ambiguity tolerance between these 2 distinct professional populations. 3 We agree with Stephens and colleagues that caution should be exercised when scales with questionable reliability and validity are used for high-stakes decisions. However, there is a risk that we might discount promising research tools, such as the TAMSAD, if we do not consider the contexts in which they have been applied to previously and the implications of these contexts on the findings.…”
Section: Context Matters: the Impact Of Context On Uncertainty Tolera...supporting
confidence: 53%
See 2 more Smart Citations
“…This was supported in our previous study that compared ambiguity tolerance between these 2 distinct professional populations. 3 We agree with Stephens and colleagues that caution should be exercised when scales with questionable reliability and validity are used for high-stakes decisions. However, there is a risk that we might discount promising research tools, such as the TAMSAD, if we do not consider the contexts in which they have been applied to previously and the implications of these contexts on the findings.…”
Section: Context Matters: the Impact Of Context On Uncertainty Tolera...supporting
confidence: 53%
“…2 Typical meta-analytic processes require judgments for determining whether studies are similar enough to make metaanalysis sensible. 3 It is debatable whether the experiences of veterinary students are substantively unique from medical students, with evidence suggesting more similarities than differences. For instance, these populations have similar matriculation and training requirements.…”
Section: Context Matters: the Impact Of Context On Uncertainty Tolera...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there appeared to be little justification regarding changes to scale design, item inclusion, scoring or consideration of the impact this may have on scale validity in the population studied. This is problematic as it has been demonstrated that seemingly small technical decisions in scale design in this field can have significant implications for the findings …”
Section: Discussionmentioning
confidence: 99%
“…One AI software is ChatGPT, a free and widely available program said to be bringing about "the end of essays as an assignment for education." 3 The use of this software seems inevitable when applicants already spend hundreds to thousands of dollars on outside application help. 2 With little time to prepare, stakeholders must weigh the risks and benefits of ChatGPT in the application process.…”
Section: The Personal Statement In the Age Of Artificial Intelligencementioning
confidence: 99%